2004
DOI: 10.1242/dev.00877
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pufferfishOtx2cis-regulators reveals evolutionarily conserved genetic mechanisms for vertebrate head specification

Abstract: The Otx2 gene, containing a highly conserved paired-type homeobox, plays a pivotal role in the development of the rostral head throughout vertebrates. Precise regulation of the temporal and spatial expression of Otx2 is likely to be crucial for proper head specification. However, regulatory mechanisms of Otx2 expression remain largely unknown. In this study, the Otx2 genome of the puffer fish Fugu rubripes, which has been proposed as a model vertebrate owing to its highly compact genome, was cloned. Consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Comparative genomics is continuing to help localize conserved noncoding sequences with gene regulatory activity, and distant evolutionary comparisons between mammals and teleosts have proven especially efficient [1,13,15,27]. In this study we characterized a gene enhancer (Dc2) identified through human-Fugu comparative genomics, and refined the sequences necessary and sufficient for its function, as well as assessed the impact of insertional mutations on its gene regulatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genomics is continuing to help localize conserved noncoding sequences with gene regulatory activity, and distant evolutionary comparisons between mammals and teleosts have proven especially efficient [1,13,15,27]. In this study we characterized a gene enhancer (Dc2) identified through human-Fugu comparative genomics, and refined the sequences necessary and sufficient for its function, as well as assessed the impact of insertional mutations on its gene regulatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics led to the original proposal to sequence the Fugu genome in order to assist with the annotation of human genes based on comparative genomics [10]. Furthermore, the availability of Fugu genomic sequence also revealed that human-Fugu conserved noncoding sequences can be used to delineate gene regulatory sequences [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of conserved non-coding elements is unknown, on the basis of recent studies 59,[63][64][65][66] it seems likely that many regulate gene expression. If so, the above results suggest that ,50% of all mammalian HCNEs may be devoted to regulating ,1% of all genes.…”
Section: Proportion Of Genome Under Purifying Selectionmentioning
confidence: 99%
“…The clusters most often coincide with genes encoding developmental and differentiation-related transcription factors. Many HCNEs have been characterized as long-range enhancers, first in studies of individual genes (Gottgens et al 2000;Sumiyama and Ruddle 2003;Kimura-Yoshida et al 2004;Milewski et al 2004), followed by systematic studies in zebrafish, Xenopus, and mouse (de la Calle-Mustienes et al 2005;Shin et al 2005;Woolfe et al 2005;Pennacchio et al 2006). Genome-wide analyses of HCNE sequences have detected several overrepresented motifs that are believed to be associated with context-specific enhancer activity (Bailey et al 2006;Pennacchio et al 2007).…”
mentioning
confidence: 99%
“…The emerging model is that an array of HCNEs defines a region of regulatory inputs of its target gene(s), and that the full complement of those inputs results in the actual expression pattern of the gene (Kimura-Yoshida et al 2004;de la CalleMustienes et al 2005;Woolfe et al 2005;Pennacchio et al 2006). It is plausible to speculate that the genes with the most complex spatiotemporal expression should have more complex regulatory inputs.…”
mentioning
confidence: 99%